The Role of Self Acceptance in Mediating The Influence of Gratitude and Social Support on Subjective Well-Being - Zellawati, Alice; Sugiharto, Dwi Yuwono Puji; Mulawarman, Mulawarman; Sunawan, Sunawan (Universitas Ahmad Dahlan, 2024)
This study aims to analyze the role of self-acceptance in mediating the influence of gratitude and social support on subjective well-being. The sample criteria include mothers who have children with special needs, specifically those with children aged 1 to 12 years. The total number of samples used was 102 participants. The sampling technique employed was purposive sampling. The instruments used to measure the subjective well-being variables were the SWLS (Satisfaction with Life Scale) and PANAS (Positive Affect Negative Affect Schedule). The gratitude variable was measured using the Gratitude Questionnaire (GQ-6), while social support was assessed using the MSPSS (Multidimensional Scale of Perceived Social Support). Self-acceptance was measured using the Porter Parent Acceptance Scale (PPAS). Data analysis was conducted in the form of mediation analysis using JASP version 18.3. The results showed that self-acceptance significantly mediated the influence of gratitude and social support on subjective well-being. The magnitude of the influence of gratitude and social support on self-acceptance was 63.7%, while the combined influence of gratitude, social support, and self-acceptance on subjective well-being was 97.4%. This indicates that the role of gratitude and social support, with the mediation of self-acceptance, is substantial in shaping subjective well-being for mothers who have children with special needs. The findings of this study are also recommended for the development of counseling guidance science by emphasizing mothers' self-acceptance to foster positive subjective well-being.